Development of the service sector and its role in consolidating global economic growth (2013)
The relationship between domestic trade and service production, on one hand, and productivity per worker and world economic growth, on the other, is studied in this paper through a panel data econometric analysis -- Two mechanisms are described where services, by incorporating technology in the productive structure of domestic economies, increase average productivity per worker and promote economic growth -- Data corresponding to 124 countries, between 1970 and 2007 was analyzed -- Significant evidence was found about the role of both imported services and domestic service production in consolidating the nations’ average productivity -- Likewise, services with a high content of human capital, as opposed to economic activities in the primary and secondary sectors, were found to underpin the largest share of productivity growth per worker in high and middle income countries